IJARAH DALAM KEUANGAN ISLAM - Choirunnisak Choirunnisak; Azka Amalia Jihad (STAI Bumi Silampari, 2020)
This study aims to find out how Ijarah in Islamic finance. This research is a type of library research (libraty research) which focuses on qualitative data management with data analysis methods using descriptive-analysis method. The results of this study are: In Banking, two types of Ijarah. The first ijarah is done in cash between the bank as a renter and the one who rents out services. The second ijarah is made in installments between banks as tenants to customers. The bank also takes advantage of this ijarah transaction. Islamic banks that operate ijarah products do leasing, both in the form of operating leases or financial leases. But in general, more Islamic banks use ijarah vomiting tamlik bit (IMBT) because it is simpler in terms of bookkeeping. Ijarah contract development is also known as ijarah muntia bi at-tamlik (IMBT).